Income smoothing and market perception of accounting numbers : an empirical investigation of extraordinary items / Wan Adibah Wan Ismail, Khairul Anuar Kamarudin and Muhd Kamil Ibrahim - Wan Ismail, Wan Adibah; Kamarudin, Khairul Anuar; Ibrahim, Muhd Kamil (Faculty of Accountancy, 2005)
This paper examines issues related to the reporting of extraordinary items in the financial statements of Malaysian companies. The first issue concerns the change of accounting standards on extraordinary items, which has limited the scope of extraordinary items. It is found that there are significant changes on the incidence of reported extraordinary items during the period after the adoption of the new standard. The findings supported the argument that the new standards on extraordinary items had consequently reduce significantly these items from financial statements. This paper hypothesizes that extraordinary items classification choice is a means used by companies to smooth income. Two types of statistical tests performed have confirmed the proposition that the disclosure of extraordinary items is subject to this type of manipulation during the period before the adoption of the new standard. Although it is proved that the broad definition of extraordinary items allows companies to manipulate income, evidence gathered from multivariate regressions demonstrates that extraordinary items are of value-relevance for investors in valuing a firm's equity. Thus, investors take into account the extraordinary items even though it is disclosed 'below the line'.